ERIOCAULACEAE OF RICE FIELDS OF BILASPUR IN CHHATTISGARH - Moghe, Snehal; Dubey, Veenapani (Current Botany, 2017)
During our field visits in Rice fields of Bilaspur, Chhattisgarh we found 3 species of Eriocaulon belonging to family Eriocaulaceae, commonly known as â€˜Pipe wortâ€™ family (Haines,1921). Though it was not very common, itâ€™s interesting and complicated morphological features made us to view this species from a different angle. These have been discussed in present paper. Keys words:Â Eriocaulon, rice field, Pipeworts, Eriocaulon quinguangulare.